Estudos metabolômicos entre interações da rizosfera de Senna spectabilis e rizobacterias associadas - Pavani, Victor Damasceno [UNESP] (2014)
Nowadays, advanced technologies are developed for the discovery of unexplored natural sources (e.g. rhizosphere microbial interaction and marine organisms), targeting new chemotherapeutic agents. In this work, Senna spectabilis’s seedlings were cultivated in hydroponic environment, and its rhizosphere’s microflora collected at three different stages of the plant’s development. It was possible to isolate 51 bacterias and 129 fungi and, after identification by phylogenetic (16S rRNA), was determined the main genders, such as Shigella, Pseudomonas, Stenotrophomonas, Bacillus, Burkholderia, Pseudoxanthomonas, Arthrobacter, Achromobacter and Rhizobiu. We chose three of bacterias, coded as CSP-50a, CSP-52b and CSP- 53b, for kinetic’s studies, aiming the comparison between the bacteria growth and the production of metabolites. This analysis showed that they reached the stationary phase at an average of 40 hours, when the production of secondary metabolites started. To characterize those metabolites, the three strains were grown on liquid nutrient medium at 25°C under agitation to achieve the phase of interest, followed by liquid-liquid partition with ethyl acetate. Analysis by mass spectrometry was performed aiming the detection and characterization of the major metabolites. It was possible to detect 08 compounds and identify 02. Metrophene acid, as well as an isomeric formamide series were detected. Additionally the formamides were also confirmed by the use of a preliminary methodology using NMR dereplication tool.